PENGARUH PERTUMBUHAN EKONOMI, PERTUMBUHAN PENDUDUK, PERTUMBUHAN INVESTASI, DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP KETIMPANGAN DISTRIBUSI PENDAPATAN DI DAERAH ISTIMEWA YOGYAKARTA TAHUN 2007-201 - Anggina, Del; Artaningtyas, Wahyu Dwi (Buletin Ekonomi Manajemen, Ekonomi Pembangunan, Akuntansi, 2017)
The Influence of Economic Growth, Population Growth, Investment Growth, and Human Development Index on Inequality of Revenue Distribution in Daerah Istimewa Yogyakarta Year 2007-2014. This research is descriptive, the approach used in this research is quantitative approach because the research data in the form of numbers and analysis using statistics. The secondary data used in econometric analysis in this study is panel data in annual form. Time series data is used from 2007-2014. Cross section data includes 5 districts / cities in Yogyakarta Special Region. The results showed economic growth and population growth did not affect the inequality of income distribution in the District / City of Daerah Istimewa Yogyakarta Year 2007-2014. Investment growth has a negative and significant effect on income income inequality in the District / City of Daerah Istimewa Yogyakarta Year 2007-2014. Human Development Index (HDI) has a positive and significant effect on income income inequality in the District / City of Daerah Istimewa Yogyakarta Year 2007-2014.Â